Community Participation in Planting of Mangroves - Sajriawati Sajriawati; Astaman Amir; Edy H.P Melmambessy; Siti Masiyah (Faculty of Agriculture Musamus University, 2020)
Research on community participation in mangrove planting in Payum Coastal aims to find out who is involved in planting mangroves and what are the stages in planting mangrove seedlings. This research was conducted in the Payum Coastal of Merauke Regency for 5 (five) months from July to November 2015. The research used survey methods and direct interviews with the community. The object of research is the people who live in the Payum Coastal Region along with traditional institutions as key figures of the study. Analysis of the data used is descriptive analysis by reporting research findings in the form of pictures and writings that describe something that is ongoing when the research is conducted. The results showed that direct community participation in mangrove management was carried out through mangrove planting based on local wisdom by the community in Payum Coastal. Activities carried out by indigenous peoples, traditional leaders, women and children. Mangrove seedlings planting activities consist of 4 (four) stages, namely nursery / seeding, bringing mangrove seedlings to the planting location, planting activities, and maintenance activities.